Superovulatory response and embryo production efficiency in goats following pretreatment with heG and estradiol-I7B - KHARCHE, S D; MAJUMDAR, A C; TYAGI, S; SHARMA, G TARU (The Indian Journal of Animal Sciences, 2011)
The yield of transferable embryos following superovulation were investigated in adult (age 2-4 years; body weight 25-35 kg) cycling goats (48) under semi arid environmental conditions of the India, by administering different superovulatory regimens. Goats were reared under intensive system of management in established farm conditions. Cyclic goats received decreasing doses of total 20IU FSH over 3 days (4+4, 3+3, 3+3 IU). The prostaglandin F2a (1.25m!) was administered i/m at 60h after the first FSH injection. Four different pretreatments were carried out (groups 2-5). Pretreatment (groups) consisted of (2) 500 IV heG i1m and 1 mg estradiol-17B sic for the next 2 days, (3) 500 IU heG i/rn and 6 h later 2 mg estradiol-17B sic, (4) as (3) but with 1 mg estradiol-17B sic, and (5) as (4) but with 250 IU heG i/rn. Goats were observed for the onset of oestrus with an aproned buck twice a day at 12h interval. The animals of group 1 and 2 were administered 500 IU hCG i/m at the synchronized estrus, numbers of visible corpora lutea (eL) and large unovulated follicles were counted and their genitalia were flushed using a standard collection procedure. The mean number of total and transferable embryo recovery in groups 1-5 were statistically significant indicating that pretreatment with low doses of heG and estradiol-17B may enhance superovulatory response in goats with regard to yield of total and transferable embryos.,p/>